Sacred power, sacred space : an introduction to Christian architecture and worship - Kilde, Jeanne Halgren, 1957-; ebrary, Inc. (New York : Oxford University Press, 2008)
Jeanne Halgren Kilde's survey of church architecture is unlike any other. Her main concern is not the buildings themselves, but rather the dynamic character of Christianity and how church buildings shape and influence the religion. Kilde argues that a primary function of church buildings is to represent and reify three different types of power: divine power, or ideas about God; personal empowerment as manifested in the individual's perceived relationship to the divine; and social power, meaning the relationships between groups such as clergy and laity. Each type intersects with notions of Christian creed, cult, and code, and is represented spatially and materially in church buildings.Kilde explores these categories chronologically, from the early church to the twentieth century. She considers the form, organization, and use of worship rooms; the location of churches; and the interaction between churches and the wider culture.Church buildings have been integral to Christianity, and Kilde's important study sheds new light on the way they impact all aspects of the religion. Neither mere witnesses to transformations of religious thought or nor simple backgrounds for religious practice, church buildings are, in Kilde's view, dynamic participants in religious change and goldmines of information on Christianity itself.
1, A Method for Thinking about Power Dynamics in Christian Space -- 2, Early Christian Meeting Space in the Roman Empire -- 3, Imperial Power in Constantinian and Byzantine Churches -- 4, From Abbey to Great Church, Fortress to Haevenly City -- 5, Transformations of the Renaissance and Reformation -- 6, Formalism and Non- or Antiformalism in Worship and Architecture -- 7, Historicism, Modernism, and Space -- 8, Concluding Observations
Obsahuje bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: dějiny architektury; církevní architektura; prostor (architektura) -- náboženské aspekty; kostely; umění a náboženství; křesťanské bohoslužby; history of architecture; church architecture; space (architecture) -- religious aspects; churches; art and religion; Christian worships; monografie; e-knihy online; monographs; e-books online